A Study on Designing, Development and Testing of an Innovative External Jig for the Percutaneous Screw Fixation of the Acetabular Column Fractures - Aditya Kekatpure1 , Sandeep Shrivastava2 , Aashay Kekatpure3 , Sunil Nikose4 , Kiran Saoji5 , Ashish (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Operative treatment of acetabulum fractures often requires open surgical fixation. Minimallyinvasive surgery (MIS) with percutaneous screw fixation can be done is some acetabular column fractureswhich are amenable to closed reduction. This can be done free hand using intraoperative fluoroscopy or withthe help of advanced 3D navigation system. Free hand technique exposes the operative staff to considerableintraoperative fluoroscopy,has a steep learning curve and there is a risk of screw malpositioning. Eventhough 3D navigation is highly accurate, the affordability of the navigation system in a rural set up is notfeasible. Use of an external universal modular jig which has been routinely used for the fixation of longbone fracture, can give similar results in the fixation of undisplaced/minimally displaced acetabular columnfractures amenable to close reduction. Currently such jigs are not available for the management of acetabularfractures.Objectives: With this study we aim to design a modular jig for the percutaneous fixation of the acetabularcolumn fracture fixation. Also we will validate in vitro efficacy and safety on cadaveric models. To test theclinical efficacy on minimally displaced acetabular column fractures.Methodology: It will be an observational study conducted at the Department of Orthopaedics, JNMC,Sawangi and Wardha, India. A 3 D model of the pelvis will be made based on the CT scan data of 40patients using Mimics 10.01 software (Materialize, Leuven, Belgium) software. After the desired jig ismade,its accuracy will be checked on the saw bone and cadaveric model. Once the accuracy of the jig hasbeen established, it will be used on the suitable patient population and the results will be compared withthe matched patient population who have been operated using the traditional free hand technique underfluoroscopy control.Results: The results will be compared based on the operating time,radiation exposure,hospital stay andpostoperative outcome. During follow up,patients in both the groups will be evaluated clinically with Harris hip score (HHS) and radiologically withMatta outcome grading. To evaluate functionaloutcome patients the patients will be categorizedinto excellent (HHS, 90-100), good (HHS, 80-90), fair (HHS, 70-80) and poor (HHS, <70).Conclusion: This study will help in designing and development of an universal external modular jig for theMIS and percutaneous fixation of acetabular column fracture.